2023
DOI: 10.3390/ijms24021417
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Biology of Cancer Stem Cells of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death globally. The cancer stem cells (CSCs) of HCC are responsible for tumor growth, invasion, metastasis, recurrence, chemoresistance, target therapy resistance and radioresistance. The reported main surface markers used to identify liver CSCs include epithelial cell adhesion/activating molecule (EpCAM), cluster differentiation 90 (CD90), CD44 and CD133. The main molecular signaling pathways include the Wnt/β-catenin, transforming growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…Cancer stem cells orchestrate a spectrum of crucial roles in hepatocellular carcinoma growth, invasion, metastasis, recurrence, and therapy resistance [ 44 ]. C .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells orchestrate a spectrum of crucial roles in hepatocellular carcinoma growth, invasion, metastasis, recurrence, and therapy resistance [ 44 ]. C .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that AFP can enhance the expansion of LCSCs by activating the PI3K/Akt signaling pathway ( 39 , 40 ). To investigate the impact of AFP on LCSCs, researchers measured the AFP expression in HCC cells firstly, then demonstrated that AFP not only facilitates the expression of proteins associated with cell reprogramming but also promotes the expression of LCSCs markers, including CD44, CD133, and EpCAM.…”
Section: The Role Of Afp In the Tme Of Hccmentioning
confidence: 98%
“…TGFβ orchestrates the initiation of EMT across various GI malignancies, including GC, CRC and HCC ( Calon et al, 2015 ; Krzysiek-Maczka et al, 2019 ; Jeng et al, 2023 ). It directly upregulates the production of multiple EMT transcription factors such as SNAIL, TWIST, SLUG and ZEB1 ( Lee and Massague, 2022 ; Trelford et al, 2022 ), and also promotes EMT by introducing epigenetic alterations.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Notably, the Notch pathway exhibits dual effects in tumor progression, acting as an oncogene or a tumor suppressor depending on varied receptor/ligand expressions or upstream regulators ( Li et al, 2023c ). Aberrant overexpression of Notch, as observed in GC, PDAC, CRC and HCC ( Vinson et al, 2016 ; Hibdon et al, 2019 ; Tyagi et al, 2020 ; Chung and Xu, 2023 ; Jeng et al, 2023 ), relates the Notch gene to tumor types characterized by increased aggressiveness, promoted drug resistance and poor clinical prognosis. The Notch pathway upregulates CSC activities by interacting with CSC surface markers.…”
Section: Signaling Pathwaysmentioning
confidence: 99%